Investigation into effects of non-uniform irradiance and photovoltaic temperature on performances of photovoltaic/thermal systems coupled with truncated compound parabolic concentrators. (15th September 2019) - Zhang, Gaoming; Wei, Jinjia; Wang, Zexin; Xie, Huling; Xi, Yonghao; Khalid, Muhammad
Highlights: Irradiance profiles of concentrators and their non-uniformities were obtained. A discrete two-dimensional electrical-thermal coupled model was developed. PV temperature distribution was obtained and its non-uniformity was evaluated. To a certain degree, non-uniform irradiance caused obvious efficiency decline. Abstract: This work concerns a type of efficient and promising solar energy utilization systems namely concentrating photovoltaic/thermal (CPV/T) systems. In CPV/T systems, uneven irradiance and PV temperature introduced by concentrators cause a rise in ohmic loss, decrease in PV fill factor and electrical efficiency, and local hot spot. Thus, the objective of this work is to develop a two-dimensional optical-thermal-electrical coupled model to predict PV temperature distribution and investigate effects of non-uniform irradiance and temperature on performance of linear concentrating CPV/T systems. Firstly, rays tracing of two kinds of truncated compound parabolic concentrators (CPCs) with different concentration ratios was simulated by TracePro to obtain their irradiance profiles. These two kinds of CPCs were designed and defined as HEMR and LEMR respectively in our previous work. Then, rays tracing results namely non-uniform irradiance distributions functioned as the inputs of a two-dimensional electrical-thermal coupled model developed by FORTRAN to obtain temperature distribution of PV array and performances of CPV/T systems. Meanwhile, a CPV/T prototype was set up to validate the theoretical results. The degrees of illumination and PV temperature non-uniformity were weighed based on the concept of standard deviation. Ultimately, the effects of non-uniform irradiance and temperature on performances of the CPV/T system were investigated with different concentration ratios. Results revealed that with a rise in concentration ratio, irradiance and PV temperature non-uniformity in the case of LEMR concentration experience a rapider increase than those in the case of HEMR concentration. Correspondingly, with increasing concentration ratios, both the fill factor and the electrical efficiency in the case of LEMR concentration experience a rapider decrease than those in the case of HEMR concentration. When the concentration ratio was 8, compared to HEMR concentration case, non-uniformity of irradiance and PV temperature in the case of LEMR concentration is increased by 63.1% and 65.7% respectively; the fill factor and the electrical efficiency in the case of LEMR concentration are decreased by 2.6% and 2.1% respectively.